2013
DOI: 10.1038/nature12776
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes mediate synapse elimination through MEGF10 and MERTK pathways

Abstract: To achieve its precise neural connectivity, the developing mammalian nervous system undergoes extensive activity-dependent synapse remodeling. Recently microglial cells have been shown to be responsible for a portion of synaptic remodeling, but the remaining mechanisms remain mysterious. Here we report a new role for astrocytes in actively engulfing CNS synapses. This process helps to mediate synapse elimination, requires the Megf10 and Mertk phagocytic pathways, and is strongly dependent on neuronal activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
950
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,071 publications
(1,030 citation statements)
references
References 37 publications
17
950
2
4
Order By: Relevance
“…Thus, a low PAP motility favors spine persistence. Interestingly, it was recently found that increased synaptic activity could promote engulfment and elimination of excitatory synapses by astrocytic processes [20]. Although PAP motility was not specifically assessed in these experiments, this suggests that astrocytic processes, depending on their level of activation and interaction with synapses, could contribute either to spine pruning and elimination or to long-term spine persistence.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, a low PAP motility favors spine persistence. Interestingly, it was recently found that increased synaptic activity could promote engulfment and elimination of excitatory synapses by astrocytic processes [20]. Although PAP motility was not specifically assessed in these experiments, this suggests that astrocytic processes, depending on their level of activation and interaction with synapses, could contribute either to spine pruning and elimination or to long-term spine persistence.…”
Section: Discussionmentioning
confidence: 78%
“…However, other studies have also proposed different mechanisms to account for a contribution of astrocytes to plasticity and memory [17,18]. Additionally, recent studies also suggest that astrocytes could participate, during development, in the formation of synaptic networks by regulating synaptogenesis [19] and spine pruning [20]. Altogether, these data indicate an important functional role of astrocytes in their interactions with synapses, despite a lack of clear mechanistic insight.…”
Section: Introductionmentioning
confidence: 66%
“…Furthermore, our finding of reactive astrocytes actively enwrapping, internalizing and further degrading presynaptic dystrophies in the APP/PS1 mouse brain is an extension of the capacity of astrocytes to phagocytose synapses as a normal process that mediates the refinement of neural circuits in the developing (Chung, Allen, & Eroglu, 2015) and in the adult CNS (Chung et al, 2013), thus suggesting a major role of astrocytes in synaptic pruning in health and disease. Supporting a phagocytic role for reactive astrocytes in AD, it has been suggested that they could mediate Aβ clearance (Osborn et al, 2016) and limit amyloid deposits (Xiao et al, 2014) since these glial cells express many potential phagocytic receptors that bind Aβ (Jones, Minogue, Connor, & Lynch, 2013; Sokolowski & Mandell, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Recently, direct evidence implicating CXCL12/SDF1 in preclinical models of anxiety and other neuropsychiatric disorders have been published (Guyon, 2014;Yang et al, 2016). Astrocytes have recently been implicated to have a role in synaptic elimination during brain development in a manner similar to the role played by the microglia in developmental pruning (Chung et al, 2013).…”
Section: Synaptogenesis Gliotransmission and Circuit Integrationmentioning
confidence: 99%